COMBINED SYSTEM ENERGY CONSUMERS USING TRADITIONAL AND ALTERNATIVE SOURCES OF ENERGY AND BATTERIES - Antipov, E. (Energy and Automation, 2016)
The possibility of creating energy-efficient systems, power supply of consumers using solar energy and battery power. The necessity of the use of heat accumulators, which works on phase transitions heat accumulating material in the composition of these systems.